Extractive Spectrophotometric determination of Cobalt (II) with p-Methylisonitroso acetophenonehydrazone - Lokhande, R.S.; Jaywant, A.S.; Barhate, V.D. (Asian Journal of Chemistry, 2010)
A simple and rapid extractive spectrophotometic method for the determination of Co(ll) is described. The complex formed between Co(Il) and p-methylisonitrosoacetophenonehydrazone is extracted into chloroform from aqueous solution of pH 7.5. The extracted species has an absorption maximum at 520 nm and obeys Beer's law over a range of 0.2-6 μg mL -1 of Co(II); the molar absorptivity being 18.3 x 103 L mole-1 cm-1. Interference from foreign ions has also been studied.